Design and Development of Competitive Electricity Market Model for Nepal - Bhatta, Ashish; Chapagain, Kamal (Journal of Science and Engineering, 2025)
In recent years, several efforts have been made to introduce a competitive wholesale electricity market in Nepal through the new electricity bill. However, in-depth studies on competitive electricity markets in the context of Nepal are almost nonexistent. This study tries to fill this research gap by developing a competitive wholesale electricity market model for Nepal. In this study, the market model is designed by dividing Nepal into six different bidding zones based on different provinces of Nepal. Two different types of pricing schemes, a uniform pricing scheme and a zonal pricing scheme, are implemented in the developed model. The study is based on the simplified model of the Interconnected Nepal Power System (INPS). The network is simplified by aggregating all the generators and loads within the same province and including the maximum power transfer capacity between two provinces. The results for two different schemes are compared based on the total cost of generation, energy surplus to the suppliers, and overall network losses. The result found that the uniform pricing schemes could lead to a lower production cost and higher network losses. The solution of a uniform pricing scheme was also found to be violating the transmission line constraint between Lumbini and Sudurpashim Province, leading to network congestion, signifying the need for re-dispatching and incurrence of dispatching costs in the uniform pricing model. The zonal pricing scheme results in lower network losses and lower surplus to suppliers and increases in overall production cost. These findings might be useful in the future for the implementation of a competitive wholesale market in Nepal.